Заповідна екзотична дендрософлора EX SITI Українського полісся (аналіз структури, оцінка декоративності, фітоценодизайн) - Савоськіна, Анна Михайлівна (НУБіП України, 2019)
Дисертація на здобуття наукового ступеня кандидата біологічних наук зі спеціальності 06.03.01 «Лісові культури та фітомеліорація». Національний університет біоресурсів і природокористування України. Київ, 2019. Дисертацію присвячено дослідженню видового складу екзотичної дендросозофлори штучних об’єктів природно-заповідного фонду Українського Полісся для з’ясування особливостей їхнього структурного флористичного аналізу, особливостей культивування, збереження, збагачення та використання у фітоценодизайні. У дисертації вперше виокремлено групи штучних заповідних парків природно-заповідного фонду Українського Полісся у сучасній їх мережі; історичні напрями інвентаризаційних досліджень заповідних дендросозоекзотів; установлено кількісний і якісний склад видів дендросозоекзотів, у тому числі вікових, які охороняються відповідно до міжнародних «червоних списків»; проведено комплексний структурний аналіз заповідної екзотичної дендросозофлори, з’ясовано сучасний стан репрезентативності культивування її видів; проведено аналіз життєздатності та виявлено інвазійні властивості окремих дендросозоекзотів; здійснено оцінку декоративності дендросозоекзотів та конструювання дендроценокомпозицій за їх участю
A thesis for the degree of candidate of biological sciences in specialty 06.03.01 «Forest Plantations and Phytomelioration». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2019. The thesis is devoted to reveal the quantitative and qualitative composition of rare exotic dendrosozoflora ex situ of artificial objects of Natural Reserve Fund of Ukrainian Polissya. Field and laboratory study were conducted during 2014–2019 years. As a result of the inventory, the general list, conspectus and catalogue of dendrosozophytes of artificial objects of Natural Reserve Fund of Ukrainian Polissya and the structural floristic analysis of the dendrosozoflora ex situ were made. In this thesis for the first time identified the historic lines of research of inventory studies of rare dendrosozophytes of Ukrainian Polissya; the quantitative and qualitative species composition of rare dendrosozophytes, including centuries-old trees, protected under the international «red lists» was established; the complex structural analysis of exotic dendrosozoflora was made and the current state of representativeness of studied species was analyzed; the assessment of decorativeness of dendrosozophytes was done. The modern network of reserved artificial objects of Ukrainian Polissya is not fully formed representatively by all categories yet and needs to be optimized. The feature of the current categorical structure of this network is that some categories of Natural Reserve Fund are represented by artificial garden objects. The exotic dendrosozoflora of the Nature Reserve Fund of Ukrainian Polissya has 105 species belonging to 39 genera, 19 families, 17 orders, three classes (5 subclasses) and 2 divisions. Pinophyta division has 62 species (59.0 % of the total species), Magnoliophyta – 43 species (41.0 %). In the biomorphological structure of the dendrosozoflora ex situ of The Natural Reserve Fund of Ukrainian Polissya by K. Raunkier predominate phanerophytes (megaphanerophytes, mesophanerophytes, microphanerophytes, nanophanerophytes). According to I. G. Serebryakov's classification, three types of life forms were found: trees, shrubs and woody vines. The type of trees is predominant and includes 94 species (89.5 %). The group of shrubs has 12 species (11.4 %). Rare dendrosozophytes of artificial objects of the Ukrainian Polissya Natural Reserve Fund are autochthons in the natural conditions of the Boreal, the Middle Mediterranean and the Madreans and the seven floristic regions, as well as the Caribbean floristic region of the Neotropic Kingdom. One floristic area belongs to 71 species (67.6 %), two species – 29 (27.6 %) species, three to four species (3.8 %). One species (Vitis vinifera L.) has an indeterminate region of origin, although archaeological information in Western Asia and Europe, it is cultivated since the Bronze Age. Representatives of the East Asian floristic region, which have 26 (24.8 %) species, predominate. Depending on the degree of demand of plants to the conditions of humidification, hree main groups of dendrosozoexotic were found: xerophytes, mesophytes and hygrophytes. The priority of the species is included in the group of mesophytes (41.0 %). The ecological group of winter-resistant plants (0–I points) belongs to the main part (91 species, 86.7 %). Types of the Circumborreal and Northwest Atlantic North American floristic areas are winter-resistant. Analyzing frost resistance, it was discovered that the group of frost-resistant species that can withstand a decrease in temperature to −25 to −35 °C prevails. Such as 74 species (70.5 %). Among the investigated rare species of plants dominated mesotrophy – 47 (45.0 %). The phytocenotypic analysis of the dendroexsozoflora of artificial objects of the Ukrainian Polissya natural reserve fund showed that of the 105 species of dendrosozoexotics, 64 (61.0 %) species are monophytocenotypic, and 38 (36.2 %) species of biphytocentric species. Three species belong to the group of triphytocenotypic. Protected by the Red List of the International Union for the Conservation of Nature and Natural Resources are 104 (99.0 %) species. The European Red List protects two species; they are classified as rare (Picea omorica (Panc.) Purkyne, Forsythia europaea Degen et Bald.). Only one species (Picea omorica (Panc.) Purkyne) is protected by both red lists. The vast majority of investigated species (76) are classified as low risk (LC) species. Most of the rare dendroexsotics ex situ have a few localities of occurrence. Single localities of 53 species of dendrosozoexotics are cultivated mainly in the Botanical Garden of Zhytomyr Agroecological University and the Bereznivsky arboreta and «Elita». In the Ukrainian Polissya, 12 species of exotic age trees were found that grow in both natural and artificial objects of the nature reserve fund in small groups of 2–5–7 individuals. They are found in solitariums, alley plantations, ordinary landings and groves. The main part of dendrosozoexotics is quite decorative, but their location is isolated in the studied areas, often in the form of tapeworm cannot express fully their decorative properties. Therefore, it is appropriate to create phytocenocompositions with highly decorative dendrosozoexotics who also have scientific value. In developing dendrophytocenocompositions main task is to enrichment plantings by the species of gymnosperms and angiosperms shrubs. Among the identified dendrosozoexotics small portion went to decorative flowering plants, as appropriate to replenish collections dendroflora synthetic natural reserve fund of Ukrainian Polissya broader species composition of woody plants, including flowering shrubs. It can be dendrosozoexotics following types: Magnolia kobus DC., Sibiraea altaensis (Laxm.) Schneid., Liriodendron tulipifera L., Forsythia europaea Degen et Bald., Malus niedzwetzkyana Dieck, Malus sieversii (Ledeb.) M. Roem and other. Creating dendrophytocenocompositions, including solitaire, groups with these species in conjunction with creeping forms gymnosperms greatly enhance the decorative plantings representation of the objects and cultivated dendroflora piece of protected parks in Ukrainian Polissya
Keywords: дендрофлора; раритетні дендроекзоти; Українське Полісся; природно-заповідний фонд; репрезентативність; декоративність; dendroflora; rare dendroexotics; Ukrainian Polissya; natural reserve fund; representativeness; decorativeness